EARLY DETECTION OF TUBERCULOSIS APPLICATION (E-TIBI): A NEW PARADIGM TO DETECT NEW CASE OF TUBERCULOSIS: Aplikasi Deteksi Dini Tuberkulosis (E-TIBI): Paradigma Baru untuk Menemukan Kasus Baru Tuberkulosis - Erwin Astha Triyono; MVS Mahanani; Sulvy Dwi Anggraini; Hafidh Maulana; Wahyu Dian Pratiwi; Christian Yochanan; Feriawan Tan; Lilis Masyfufah (Jurnal Berkala Epidemiologi, 2023)
Background: Tuberculosis (TB) is still one of the major health problems in the world, especially in countries with dense populations. Indonesia is listed among the top three countries with the highest burden of tuberculosis worldwide. The low coverage of case detection in Indonesia is one of the reasons for ineffective TB control. Therefore, this disease remains a threat to spread in today's Indonesian society. Digital technology can be used to increase the effectiveness and efficiency of case detection. This study aims to create a new paradigm for detecting new cases of tuberculosis using a self-assessment website-based application. Methods: This descriptive quantitative research used univariate analysis. Respondents for this research were sampled from all East Java people who filled out the E-TIBI application. Result: In total, there were 4,658 E-TIBI users in East Java, with 20.80% suspected of tuberculosis. The most frequent symptoms found in the respondents were fatigue, cough for > 2 weeks, and weight loss. Discussion: A self-assessment paradigm based on digital technology was applied to the design of this E-TIBI application. From this application, the public can quickly determine whether they or others are suspected of having tuberculosis. This result shows that the whole community can easily access the E-TIBI application for initial tuberculosis screening. Conclusion: Through this application, direct community participation can increase the detection of new cases to support the government and WHO programs in eliminating tuberculosis by 2030.